Did Performing Community Health Needs Assessments Increase Community Health Program Spending by North Carolina's Tax-Exempt Hospitals? - Fos, Elmer B; Thompson, Michael E; Elnitsky, Christine A; Platonova, Elena A (Population health management, 2019)
As of March 23, 2012, the Internal Revenue Service (IRS) requires tax-exempt hospitals to conduct a Community Health Needs Assessment (CHNA) every 3 years. This study assessed whether the IRS CHNA mandate incentivized North Carolina's tax-exempt hospitals to increase investments in community health programs. The authors gathered the 2012-2016 community benefit reports of 53 North Carolina private, nonprofit hospitals from the North Carolina Hospital Association. Community benefit spending data from the year of the first CHNA were compared to that 2 years later using paired tests among matched subjects. No significant increases were found in hospitals' community health programs spending ( = 0.6920) or in providing patient care financial assistance (charity or discounted care) ( = 0.0934). In fact, aggregate community health programs spending effectively decreased by 4%, from $393.3 million to $377.5 million. Among all community benefit items, only the unreimbursed cost for treating Medicare patients increased significantly ( = 0.0297). The proportion of spending on community health programs relative to patient care financial assistance decreased significantly ( = 0.0338). Performing CHNAs did not incentivize North Carolina's tax-exempt hospitals to progressively invest in community health programs. The hospitals continue to spend heavily on patient care financial assistance and little on disease prevention and community health improvement activities. These findings suggest that tax-exempt hospitals continue to function as a safety net for the poor and the uninsured rather than as active partners in population health management initiatives. At present, performing CHNAs may be more a demonstration of compliance than a tool to improve population health.